The Construction of Agricultural Extension Competencies in Cyber Media for Community Education - Hadiyanti, Puji; Wanpeng, Lei; Sasmita, Karta; Syah, Rahmat; Jafar, Muhammad Mawardi (Journal of Nonformal Education, 2023)
This study aims to analyze the capacity of agricultural instructors in developing cyber extension media, which consists of the characteristics of cyber extension media, cyber extension media design, characteristics of self-help extension workers, and the capacity of self-help agricultural extension workers, as well as analyzing the factors that affect the ability of extension workers in developing cyber media. This research uses quantitative research through a survey method. Data analysis was carried out descriptively and inferentially using Structural Equation Models. Correlational prescriptive results explored about 108 informants. The results of SEM modelling show a direct and indirect effect on the ability of independent agricultural instructors to develop CE media. So it can be said that there is an influence of media characteristics, media design, characteristics of self-help extension workers, and the capacity of self-help agricultural instructors on agricultural instructors' performance. The correlation test results have a significant relationship between the utilization of Cyber Extension by agricultural extension workers and the capability of agricultural extension workers to have an excellent significant value.